Das griechische Dilemma: Eine spieltheoretische Betrachtung - Kristin Berthold (European University Viadrina, Department of Business Administration and Economics, 2015)
Der vorliegende Artikel untersucht die aktuelle Krise zwischen Griechenland und dem Rest der Eurozone. Ziel ist es, diesen internationalen Konflikt spieltheoretisch zu analysieren und mögliche Handlungsalternativen, verschiedene Szenarien und Folgen abzuleiten. Den Rahmen stellt das sogenannte Feiglingspiel dar. In diesem Spiel geht es um eine Mutprobe zwischen zwei Fahrern, die aufeinander zufahren. Es erfolgt eine Erweiterung des Modells, indem die Strategieoptionen und Präferenzen verändert werden. – – This article examines the current crisis between Greece and the rest of the Eurozone. Its objective is to provide a game-theoretic analysis of this international conflict and to develop alternative courses of action, different scenarios and consequences. The socalled Chicken-Game represents the analytic framework. This game illustrates a test of courage between two car drivers which drive towards each other. The model will be extended and analyzed using variations of strategy options and preferences.
Keywords: 330; Chicken-Game; Eurokrise; Griechenland